Intralesional purified protein derivative of tuberculin versus intralesional mycobacterium W vaccine in treatment of recalcitrant extragenital warts: A randomized, single-blinded, comparative study - Alpana Mohta; Suresh Kumar Jain; Rajesh Dutt Mehta; Aakanksha Arora (Wolters Kluwer Medknow Publications, 2022)
Introduction: Of late, immunotherapy has emerged as a promising therapeutic modality for the treatment of recalcitrant and difficult to treat warts. Purified protein derivative of tuberculin (PDD) and mycobacterium w (Mw) vaccine hold promising prospects for the treatment of verruca, especially in a country like ours where a majority of the population is already sensitized to mycobacterium tuberculosis both due to disease endemicity and Bacillus Calmette-Guérin (BCG) vaccination. Aims and Objectives: We aimed at evaluating the treatment outcome of intralesional PPD tuberculin and Mw vaccine in the treatment of recalcitrant extragenital warts in immunocompetent subjects. Materials and Methods: The patients included immunocompetent subjects between the ages of 16 and 65 years with two or more extragenital warts. The patients were randomized into two groups, namely A (PPD Tuberculin) and B (Mw vaccine). In both groups, 0.1 mL of active intralesional immunogen was injected at the base of the largest wart. The doses were repeated at 4 weeks' intervals for a maximum of 5 injections. Additionally, the improvement in quality of life was measured using the Hindi-validated version of the Dermatology Quality of Life Index (DLQI) questionnaire. Results: Ninety-seven patients completed the study, with 46 in group A and 51 in group B. In group A, 24 (52.17%) patients had complete clearance in all warts, and in group B, 32 (62.75%) (P = 0.38). The most common adverse event in patients of group A was transient injection site erythema and swelling, whereas that in group B was mild transient fever. None of the patients showed any signs of recurrence in the ensuing follow-up period. There was a statistically significant improvement in the mean DLQI scores after treatment in both groups (P < 0.0001). Conclusion: Both PPD Tuberculin and Mw vaccine are effective in the treatment of recalcitrant warts with minimal recurrence rate. The safety profile of PPD is superior to Mw vaccine. We suggest both to be used as first-line therapy in the treatment of difficult to treat warts.